Analysis of the Company's Profit Level Using Risk Profile, Good Corporate Governance, Earnings, and Capital Methods - Aviliani Aviliani; Adira Nurul Izzah; Hedwigis Esti Riwayati (Dinasti Publisher, 2025)
The purpose of this study is to determine the effect of bank health using the Risk Profile, Good Corporate Governance, Profit and Capital methods on the bank's profit level. The sample of this study is a group of banks based on core capital 3 for the period 2018-2022. The analysis method used is panel data regression. The results showed that the Risk Profile proxied with the Loan to Deposit Ratio and Capital proxied with the Capital Adequacy Ratio had a significant negative effect on the level of profit, while Good Corporate Governance proxied with institutional ownership and Profit proxied with Return on Assets had a significant positive effect on the level of Profit. The Risk Profile factor proxied with Non-Performing Loans and the Profit factor proxied with Operating Expenses and Operating Income did not affect the level of profit in the group of banks based on core capital 3 for the period 2018-2022.